Elaboration of learning cycle 5E model and PJBL based on creative products and fun entrepreneurship through shutterstock application - Moningka, Yudha; Aprilia, Nani; Isnaeni, Bekti (JPGI (Jurnal Penelitian Guru Indonesia), 2024)
PKK subject is a lesson about ethics, values, skills and attitudes in facing the challenges of life to obtain opportunities in various risks faced. The implementation of "Elaboration of Learning Cycle 5E Model and PjBL based on creative products and fun entrepreneurship through shutterstock application" as an effort to guide the learning process in accordance with the times of students to find business opportunities through mobile phones in the era of globalisation and industrial revolution  4.0. This descriptive research conducted at SMK Negeri 3 Penajem Paser Utara. Research subjects  were students of Livestock Agribusiness Class XI Phase F Even Semester, 2022/2023 academic year. The object research is learning by using the 5E model based on creative product projects and fun entrepreneurship. Data collection techniques through documentation and observation. Data analysis technique is descriptive analysis. The findings showed that the project contributed to improving students' understanding and practice of entrepreneurial values.